Influence of electrochemical oxidation of carbon fiber on the mechanical properties of carbon fiber/graphene oxide/epoxy composites. (April 2017) - Jiang, Jianjun; Yao, Xuming; Xu, Chumeng; Su, Yang; Zhou, Linchao; Deng, Chao
Abstract: In this paper, the results of the surface modification of carbon fiber (CF) by electrochemical oxidation coupled with the electrophoretic deposition technique are presented. Graphene oxide (GO) was deposited on the electrochemically oxidized CF surface to improve the mechanical performance of carbon fiber-reinforced epoxy composites. The surface roughness and wettability increased after the electrochemical oxidation treatment of CF by the electrophoretic deposition technique, which was shown to be a feasible method. The results showed that a uniform distribution of GO coating was constructed and that GO was firmly coated on the CF surface through covalent attachments. In addition, the results of the mechanical properties tests showed that the interlaminar shear strength and compressive strength of the composites increased by 59.4% and 12.8%, respectively. The presented continuous fabrication process, which did not involve long processing times or complex chemical reactions, offers a potential industry compatible method for preparing multiscale GO/CF reinforcements.